Consistent patterns of debris on South African beaches indicate that industrial pellets and other mesoplastic items mostly derive from local sources. (July 2018) - Ryan, Peter G.; Perold, Vonica; Osborne, Alexis; Moloney, Coleen L.
Abstract: Identifying the sources of small plastic fragments is challenging because the original source item seldom can be identified. South Africa provides a useful model system to understand the factors influencing the distribution of beach litter because it has an open coastline with four equally-spaced urban-industrial centres distant from other major source areas. We sampled mesodebris (∼2–25 mm) at 82 South African beaches in 1994, 2005 and 2015. Plastic items comprised 99% by number and 95% by mass of litter items. Industrial pellets were the most abundant plastic items, but fragments of rigid plastic items comprised most of the mass of debris. Strong correlations between industrial pellets and other plastic items indicate that common factors influence the distribution of both pellets and secondary mesoplastics. The abundance of mesodebris at beaches also was correlated in successive surveys, suggesting that beach-specific factors (e.g. aspect, slope, local currents, etc.) influence the amounts of debris on each beach. Sample year had no effect on mesodebris abundance, indicating that there has been little change in the amounts of mesodebris over the last two decades. There were consistently higher densities of both industrial pellets and other plastic items at beaches close to urban-industrial centres; there were only weak correlations with human population density and no correlation with local runoff. The size of industrial pellets decreased away from local urban centres, further supporting the conclusion that, like macroplastic litter, most mesoplastic pollution on continental beaches derives from local, land-based sources. This finding means that local actions to reduce plastics entering the sea will have local benefits, and that it may be possible to assess the efficacy of mitigation measures to reduce marine inputs of mesoplastic items. Graphical abstract: Image 1 Highlights: Plastic items comprise 99% by number and 95% by mass of sandy beach mesodebris. Correlations between plastic pellets and other mesodebris indicate common sources. There is no evidence of an increase in mesodebris loads over the last two decades. Mesodebris is concentrated around local urban centres. The efficacy of local mitigation measures should be fairly easy to assess. Abstract : Mesoplastic pollution (∼2–25 mm) on South African beaches is concentrated around urban-industrial centres, which indicates the importance of local sources and suggests that actions to reduce marine inputs of mesoplastic items will have local benefits.